PECULIARITIES OF FORMING AN ENTERPRISE RISK MANAGEMENT SYSTEM IN THE CONTEXT OF MODERN TRANSFORMATIONS: THE EXPERIENCE OF EUROPEAN COUNTRIES AND UKRAINE - Maryna Dielini; Marja Nesterova; Wang Yi (Baltic Journal of Economic Studies)
The contemporary technological, innovative, political, economic and social development of the world has exerted a dual impact on the operations of enterprises, giving rise to both beneficial and detrimental consequences, whilst concomitantly engendering novel threats and risks. Risks are an integral part of the activities of enterprises and involve deviations from planned indicators. The consequences and types of risk are contingent on the surrounding and internal environment, and may vary depending on the scope of activities of enterprises and the country (region) of residence. The objective of this research is to analyse and study the prerequisites and features of the formation of the enterprise risk management system under the conditions of modern transformations in the EU countries and Ukraine. Research methods: analysis, synthesis, extrapolation, generalisation, graphic, dynamics analysis, content analysis, etc. The results of the study indicate that a theoretical analysis has demonstrated the acute necessity of transforming traditional risk management from a reactive to a proactive enterprise risk management (ERM). It is recommended that this ERM should become an integrated element in the company's management system, and that it should be systemic, cyclical and holistic in nature. ERM is evolving into a system that facilitates a strategic approach to risk management at all levels of enterprise management. At present, the enterprise has numerous opportunities to enhance the efficacy of risk management. However, it should be noted that these same opportunities also engender novel threats and risks. The development of information technologies has given rise to a number of potential risks for enterprises. Chief among these are the threats posed by cyber-attacks, the leakage of information, and the transfer of important data to cyberspace. In this regard, it is imperative for management to comprehend the urgency and necessity of implementing an Enterprise Risk Management (ERM) system within their enterprise. A close examination of search queries has revealed a notable interest among business representatives in issues pertaining to risk. However, it is important to note the differences between Poland, Germany, France and Ukraine. Entrepreneurs from EU countries have been observed to engage in extensive research on risk and associated search queries. Consequently, it is imperative to adopt a more profound approach in examining this matter and to establish a comprehensive risk management system on a larger scale. It is imperative to utilise diverse avenues to enhance one's qualifications in this domain, fostering collaboration with a range of stakeholders, including communities, which can serve as a valuable source for effective risk management.